2022
DOI: 10.1038/s41416-022-02016-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk of subsequent primary oral cancer in a cohort of 69,460 5-year survivors of childhood and adolescent cancer in Europe: the PanCareSurFup study

Abstract: Background Survivors of childhood cancer are at risk of subsequent primary malignant neoplasms (SPNs), but the risk for rarer types of SPNs, such as oral cancer, is uncertain. Previous studies included few oral SPNs, hence large-scale cohorts are required to identify groups at risks. Methods The PanCareSurFup cohort includes 69,460 5-year survivors of childhood cancer across Europe. Risks of oral SPNs were defined by standardised incidence ratios (SIRs), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These malignancies may develop years after pediatric cancer treatment. A large European study investigating oral cancer risk in almost 70,000 long-term CCS reported an overall 5-fold increased risk of developing oral cancer as compared to the general population [15]. Hodgkin lymphoma and leukemia survivors treated with head and neck radiotherapy were at a 33-fold increased risk of developing salivary gland tumors, whereas CCS treated with chemotherapy had a substantially increased risk of tongue cancer (RR = 5.6, 95% CI: 1.0-31.2) [15].…”
Section: Subsequent Primary Malignanciesmentioning
confidence: 99%
See 3 more Smart Citations
“…These malignancies may develop years after pediatric cancer treatment. A large European study investigating oral cancer risk in almost 70,000 long-term CCS reported an overall 5-fold increased risk of developing oral cancer as compared to the general population [15]. Hodgkin lymphoma and leukemia survivors treated with head and neck radiotherapy were at a 33-fold increased risk of developing salivary gland tumors, whereas CCS treated with chemotherapy had a substantially increased risk of tongue cancer (RR = 5.6, 95% CI: 1.0-31.2) [15].…”
Section: Subsequent Primary Malignanciesmentioning
confidence: 99%
“…A large European study investigating oral cancer risk in almost 70,000 long-term CCS reported an overall 5-fold increased risk of developing oral cancer as compared to the general population [15]. Hodgkin lymphoma and leukemia survivors treated with head and neck radiotherapy were at a 33-fold increased risk of developing salivary gland tumors, whereas CCS treated with chemotherapy had a substantially increased risk of tongue cancer (RR = 5.6, 95% CI: 1.0-31.2) [15]. A large study among recipients of allogeneic HCT found that young age at transplantation, total body radiation, and (a history of) cGVHD contributed to an increased risk of oral squamous cell carcinoma [87].…”
Section: Subsequent Primary Malignanciesmentioning
confidence: 99%
See 2 more Smart Citations